2004
DOI: 10.1088/0953-8984/16/40/001
|View full text |Cite
|
Sign up to set email alerts
|

Weak-magnetism phenomena in heavy-fermion superconductors: selected  SR studies

Abstract: The behavior of the so-called weak moment antiferromagnetic states, observed in the heavy-fermion superconductors UPt 3 and URu 2 Si 2 , is discussed in view of recent µSR results obtained as function of control parameters like chemical substitution and external pressure. In UPt 3 , the Pd substitution for Pt reveals the dynamical character of the weak moment order. On the other hand, µSR measurements performed on samples in which Th substitutes U suggest that crystallographic disorder on the magnetic sites de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 89 publications
6
83
0
Order By: Relevance
“…Let us recall the hydrostatic pressure -temperature phase diagram obtained from highpressure µSR experiments [6] (a phase diagram of the same shape results from our mean field theory, see Fig. 5, left).…”
Section: Octupolar Ordermentioning
confidence: 82%
See 3 more Smart Citations
“…Let us recall the hydrostatic pressure -temperature phase diagram obtained from highpressure µSR experiments [6] (a phase diagram of the same shape results from our mean field theory, see Fig. 5, left).…”
Section: Octupolar Ordermentioning
confidence: 82%
“…A recent µSR study [6] finds that the symmetry of hidden order is different from A 2u (Q) which is the symmetry of the high-pressure antiferromagnetic phase (the same structure was ascribed to the supposed "micromagnetism" of URu 2 Si 2 , which is now understood to be extrinsic). The present experimental status is that the intrinsic low-pressure behavior of URu 2 Si 2 is purely non-magnetic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence for the heterogeneous coexistence of the HO and AFM states below 15 kbar was suggested from 29 Si NMR measurements [16,17] and µSR measurements indicated that the AFM volume fraction emerged at ≈ 5 kbar (extrapolated to T = 0 K) [18,19]. This general pressure-dependence was corroborated by measurements of dilation under pressure [20], while measurements of ac magnetic susceptibility demonstrated the suppression of the SC state at approximately 4 kbar, at the T = 0 K onset of the HO-AFM transition [21,22].…”
Section: Introductionmentioning
confidence: 99%